Flood flow simulations and return period calculation for the Kota Tinggi watershed, Malaysia. (9th August 2016) - Abdullah, J.; Muhammad, N.S.; Julien, P.Y.; Ariffin, J.; Shafie, A.
Abstract : The City of Kota Tinggi in Malaysia was under more than 5 m of water during the floods in December 2006 and January 2007. The watershed received between 280 and 530 mm of rain in 4 days. These extreme events occurred 3 weeks apart and caused extensive damages. The application of the fully distributed two‐dimensional model two‐dimensional runoff, erosion and export (TREX) to simulate these events and the estimation of the return period of such extreme events are the main objectives of this study. The model performance was very good based on the relative percentage different (3.7%), percent BIAS (overestimated the volume by 1.5%) and Nash–Sutcliffe efficiency coefficient (0.8). The TREX model is successful in simulating extreme flood events. The December 2006 rainstorm event at Kota Tinggi is extremely rare, and this multiday rainstorm had an estimated return period greater than 2000 years. The analysis of the return period shows that multiday rainstorms occur more frequently than single‐day events. In addition, we produce a flood threshold graph by integrating both the hydrological modelling process using TREX and the theoretical formulation of return period. The proposed flood threshold graph is useful in the estimation of the amount of accumulated rainfall from multiday rainfall that can cause flooding on a large watershed like Kota Tinggi.